The population and mortality characteristics of mangrove crab (Scylla serrata) in the mangrove ecosystem of Tarakan City, Indonesia - AGUS INDARJO; Gazali Salim; MUFRIDA ZEIN; DODDY SEPTIAN; STEPHANIE BIJA (Society for Indonesian Biodiversity, 2020)
Abstract. Indarjo A, Salim G, Zein M, Septian D, Bija S. 2020. The population and mortality characteristics of mangrove crab (Scylla serrata) in the mangrove ecosystem of Tarakan City, Indonesia. Biodiversitas 21: 3856-3866. The mangrove crab is an iconic species of Tarakan City and is often is used as a souvenir. However, the high demand for this species can cause its population to decline. This study aimed to characterize the mangrove crab (Scylla serrata) population in the mangrove ecosystem of Tarakan City, North Kalimantan, Indonesia. This study was designed using a quantitative descriptive method with a case study model. The samples of mangrove crabs were obtained from 6 different stations using a purposive sampling method. The mangrove crab specimens were caught using 35-50 units of crab traps known as the ambau brackets. The primary data included carapace length, carapace width, carapace thickness, sex, and the total weight of each mangrove crab specimen. The results showed that male mangrove crabs have positive allometric growth when the condition index was fat. However, female crabs exhibited negative allometric growth when the condition index was thin. The Von Bertalanffy growth model analysis showed that the maximum carapace length of male mangrove crab in the mangrove ecosystem of Tarakan City was approximately 11.1118 cm for 189 days, while the female length was 9.6474 cm for 80 days. The total mortality value of male and female crabs was 120.01% and 154.94%, the mortality due to fishing was 84.69% and 135.75%, and natural mortality was 35.32% and 19.2%, respectively. The estimated rate of exploitation of both male and female crabs was 70.57% and 87.61%, respectively. The exploitation of S. serrata in the mangrove ecosystem of Tarakan City was evident, hence, conservation efforts are urgently required.